Brazil and Spain: Management of Public Sports Policies - Cintia Csucsuly Rocha; Wagner Barbosa Matias; Fernando Mascarenhas (Universidade Salgado de Oliveira, 2020)
The study seeks to compare the sport management model in Brazil with that in Spain. For this, a bibliographic review and a documentary study were carried out. This was done from the websites of the extinct Ministry of Sports in Brazil and the Consejo Superior de Deportes in Spain. It was observed that in both countries the occupation of positions in public bodies goes through different institutional political arrangements, according to particular characteristics and inherent to their government systems. With regard to the State's relationship with the sports administration and practice entities, we note that while in Brazil there is an autonomy of these entities, in Spain they do not have administrative autonomy. Finally, it was identified that the management logic of public sports policies has a predominantly neo-corporatist bias in Brazil and corporatist in Spain.